Effects of Voice Compression on the Operation of aN-ISDN/B-ISDN IWF - Rikli, Nasser-Eddine (Universiti Putra Malaysia Press, 2001)
The significant widespread of N-ISD , which has recently gained momentum, will make it hard for the emerging B-ISD whether to ignore its presence or to phase it out and replace it in the near foreseen future. Consequently, the ATM of the interoperability specification CES-IS V2.0 (af-vtoa-0078.000), which defines emulation standards for circuit characteristics of constant bit-rate (CBR) traffic within ATM. A critical attribute of a circuit emulation service (CES) is to achieve a performance comparable to that are still pending will be addressed. Special interest will be given to devising methods that will enable voice, which is a size able component of the current N-ISD traffic, to be carried efficiently over ATM network. First, a multiplexing technique for voice sources will be presented. Then, assuming that speech silence detection is being used, a technique for dealing with the partially filled cells wil be suggested, analyzed, and then simulated. The results will be then presented and analyzed, followed by conclusions and suggestions.